Social Accounting; Tendensi Kemaslahatan Publik dibalik Kenaikan Tarif BPJS Kesehatan di Indonesia - Majid, Jamaluddin; Saputra, Reza Eka (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2020)
Public needs about healthness rights has been usually ignored by the regulation that’s truly not being pro of people. Doubled rate increase of BPJS-Kesehatan is the one that properly will given a social effort for the people. According to the case, this study aims to know the tendention of rate increase of BPJS Kesehatan related to public needs. This article is a qualitative research with interpretive approach that try to study about problem or social issues with indepth-detail purpose. Literatur study have applied to collate the data and information. To keep the quality of data, source of data and theory of triangulation used in this study before make final results. The result show that rate increased of BPJS Kesehatan has been given a social effort like economic problem because the increase not following by income growth of peoples. In the other side, this regulary will broke the public rights if there is noy following by a prime service. Government have to make a good analysis with social accounting points as the relevance and reliable policys purpose.